Structure Characterization and Potential Probiotic Effects of Sorghum and Oat Resistant Dextrins - Wenwen Chen; Ting Zhang; Qi Ma; Yingying Zhu; Ruiling Shen (Foods, 2022)
Resistant dextrins (RDs) were prepared from sorghum and oat starches to determine their molecular structure, physicochemical properties, digestibility and prebiotics effect in vitro. The results showed that the particle size of sorghum resistant dextrin (SRD) and oat resistant dextrin (ORD) was significantly smaller than their respective starches. They formed a block structure, and lost the original A-type structure. In addition, SRD and ORD had good thermal stability, solubility (>90%) and enzymatic hydrolysis resistance (digestibility < 5%). The potential probiotic effects of ORD and SRD were studied by measurement of their promoting effects on the growth of Lactiplantibacillus plantarum, Lactobacillus acidophilus and Lactobacillus delbrueckii. For Lactiplantibacillus plantarum and Lactobacillus acidophilus, the promoting effect of ORD was the best (p < 0.05), and the counts increased by 8.89 and 8.74 log CFU/mL, respectively, compared with the control. For Lactobacillus delbrueckii, SRD was most effective, increasing the counts by 8.72 log CFU/mL compared with the control. These characteristics make SRD and ORD suitable for use as soluble dietary fiber and prebiotics in beverages and the excipients of low-glycemic-index products.